Enlicitide (Lipfendra): the first oral PCSK9 inhibitor - from macrocyclic peptide innovation to clinical translation - Divyashanthi Chellathambi Malathi; Kumaravel Janakiraman; Sathiya Vinotha Ariyur Thangavelu; Dhivya Ravichandran (International Journal of Basic & Clinical Pharmacology, 2026)
A substantial proportion of patients with hypercholesterolaemia, particularly those with atherosclerotic cardiovascular disease (ASCVD) or heterozygous familial hypercholesterolaemia (HeFH), do not achieve recommended LDL-cholesterol (LDL-C) targets despite statins, ezetimibe, and injectable PCSK9 inhibitors. The parenteral route of the latter remains a well-recognised barrier to their wider use. Objective of the study was to review the discovery, pharmacology, clinical evidence, and therapeutic positioning of enlicitide (Lipfendra), the first oral PCSK9 inhibitor, approved by the US FDA in July 2026. A structured narrative review of PubMed/MEDLINE, ClinicalTrials.gov, FDA regulatory documents, and the primary CORALreef trial publications, with priority given to original clinical and discovery-chemistry sources over secondary reviews. Enlicitide is an orally bioavailable macrocyclic peptide that binds circulating PCSK9 and preserves hepatic LDL-receptor recycling. Across the CORALreef phase 3 programme, it produced placebo-adjusted LDL-C reductions of approximately 56–60%, with concordant reductions in apolipoprotein B, non-HDL-cholesterol, and lipoprotein(a). Its short-term safety profile was comparable to placebo. Its approval further demonstrates, for the first time, that a large extracellular protein-protein interaction, previously considered accessible only to injectable biologics, can be disrupted through an orally administered peptide. Enlicitide brings potent PCSK9 inhibition within an oral formulation for the first time. Whether this translates into reduced cardiovascular events, how it performs over long-term use, and how accessible it will prove outside the United States - including in India, where familial hypercholesterolaemia remains substantially underdiagnosed - are questions that current evidence cannot yet answer.